2021
DOI: 10.1017/s0033291721000477
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of the longitudinal relationship between childhood adversity and late adolescent psychopathology

Abstract: Background Childhood adversity (CA) is commonly associated with an increased risk of subsequent psychopathology. It is important to identify potential mediators of this relationship which can allow for the development of interventions. In a large population-based cohort study we investigated the relationship between CA and late adolescent psychopathology and early adolescent candidate mediators of this relationship. Methods We used data from three waves (n = 6039) of Cohort 98′ of the Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
2
12
1
Order By: Relevance
“…None of the potential effect modifiers we examined (gender, father’s occupational social class, parental involvement, cognitive ability, conscientiousness, internalising problems, externalising problems, and physical health problems) altered the association between ACEs and trajectories of distress. Previously, these social and developmental domains have been found to partially explain the association between ACEs and psychopathology (Healy et al ., 2021, Miller et al ., 2021, Miller et al ., 2018). However, they do not appear to amplify or weaken the relationship between ACEs and adult trajectories of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the potential effect modifiers we examined (gender, father’s occupational social class, parental involvement, cognitive ability, conscientiousness, internalising problems, externalising problems, and physical health problems) altered the association between ACEs and trajectories of distress. Previously, these social and developmental domains have been found to partially explain the association between ACEs and psychopathology (Healy et al ., 2021, Miller et al ., 2021, Miller et al ., 2018). However, they do not appear to amplify or weaken the relationship between ACEs and adult trajectories of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Selous and colleagues found a stronger association between ACEs and distress for men than women at age 50 (Selous et al ., 2020). Most research typically investigates social, emotional, and neurobiological domains of the child’s development conceptualised as mechanisms (‘mediators’) explaining how ACEs may translate to later psychopathology (Healy et al ., 2021, Miller et al ., 2021, Miller et al ., 2018). In the current study, we identified the potential effect modifiers of ACEs-psychological distress associations according to the criteria – occurring in early-life, spanning multiple domains of early-life development, and having been previously studied in the context of ACEs and mental health, for instance as exposures or mediators (Atkins et al ., 2020, Barboza Solís et al ., 2016, Dodgeon et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Those who are motor-skilled, handy, agile, and can run fast are more popular among the children of younger school age (48). Along with the imrovement of their abilities among peers, the ego increases in all dimensions of quality of life (49,50). Children with acquired skills feel more comfortable when performing physical activities and they have affection to exercise, which contributes to better health, general mood, and better relationships with family and friends.…”
Section: Physical Activity and Motor Skills Relationshipmentioning
confidence: 99%
“…Adversity during this period can have profound implications for the developmental trajectory, leading to de cits later in life such as increase rates of psychopathology 2,3 . Stress during pregnancy and early life can alter behavior 4 and brain development 5 .…”
Section: Introductionmentioning
confidence: 99%